1997
DOI: 10.1038/sj.leu.2400849
|View full text |Cite
|
Sign up to set email alerts
|

t(14;18), a journey to eternity

Abstract: The t(14;18) is the most frequent chromosomal aberration observed in follicular non-Hodgkin's lymphoma (NHL), and less frequently in diffuse large cell lymphoma (DLCL). The t(14;18) does not affect overall survival in follicular NHL or DLCL. It provides a unique lymphoma-specific marker that can be used to quantify residual disease during treatment, and may forward evaluation of new treatment protocols. The t(14;18) results in the deregulation of bcl-2, a proto-oncogene that protects against induction of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 76 publications
1
27
0
Order By: Relevance
“…81 The importance of the Bcl-2 family of proteins is underscored by reports of their dysregulation in many hematological malignancies that can contribute to the resistance of such malignancies to pro-apoptotic chemotherapeutic drugs. [82][83][84][85][86][87][88][89][90] Apoptosis due to the cell receiving an abnormal proliferative signal…”
Section: The Bcl-2 Family Of Proteins: the Finger On The Buttonmentioning
confidence: 99%
“…81 The importance of the Bcl-2 family of proteins is underscored by reports of their dysregulation in many hematological malignancies that can contribute to the resistance of such malignancies to pro-apoptotic chemotherapeutic drugs. [82][83][84][85][86][87][88][89][90] Apoptosis due to the cell receiving an abnormal proliferative signal…”
Section: The Bcl-2 Family Of Proteins: the Finger On The Buttonmentioning
confidence: 99%
“…12 Approximately 60% of NHL in North America is either follicular NHL or diffuse large B-cell NHL, 13 and about 70% to 90% of follicular NHL, and 20% to 30% of diffuse large B-cell NHL have a t(14;18)(q32;q21) chromosomal translocation. 10,14 A study by Schroeder et al 15 found that the risk of NHL associated with farming and exposure to dieldrin, lindane, atrazine, or fungicides was limited only to case subjects with the t(14;18) translocation as assessed by polymerase chain reaction (PCR) analysis. 15 Those researchers suggested that NHL subtypes defined by t(14;18) status might have greater etiologic specificity than NHL in aggregate.…”
Section: Introductionmentioning
confidence: 99%
“…1 The neoplastic clone of the great majority (up to 80%) of FL patients bears the t(14;18) translocation in which the Bcl-2 proto-oncogene on chromosome 18 is translocated to the immunoglobulin heavy chain (IgH) region on chromosome 14, creating a hybrid Bcl-2/IgH gene. 2 The molecular cloning of this translocation has allowed development of a polymerase chain reaction (PCR)-based assay for the diagnosis and monitoring of minimal residual disease (MRD). 3 Despite the prolonged median survival time of these patients, 1,4,5 both conventional and experimental therapeutic approaches have failed to modify the overall survival of the disease, 6 although high-dose therapy might provide some advantage at least in terms of freedom from disease progression.…”
Section: Introductionmentioning
confidence: 99%